The Arts Therapist in Public: The Dichotomy of Clinical and Performative Improvising - Haire, Nicky; White, Becky; Derrington, Philippa (Voices: A World Forum for Music Therapy, 2017)
This paper presents a video of a performance at 'Concurrent♯2' in Edinburgh, 2017. it is followed by artist statements made in response to watching the piece. The authors' set in context the work and its development.